Sports law and policy in the European Union - Parrish, Richard (Manchester University Press, 2003)
The commercialisation of sport in Europe raises important questions concerning the most appropriate method of regulating sporting activity. The development of the European Union and the internationalisation of sporting competition has added an international dimension to this debate. Yet sport is not simply a business to be regulated in the same way as any other industry. It is also a social and cultural activity. Can regulation at EU level reconcile this tension? Adopting a distinctive legal and political analysis, this book argues that the EU is receptive to the sports sectors claims for special treatment before the law. The book investigates the birth of EU sports law and policy by examining: the Bosman ruling and other significant European Court of Justice decisions; the relationship between sport and EU competition law; the possibility of sport being exempt from EU law; the relationship between sport and the EU Treaty; the development of a EU sports policy. This book is essential for those interested in the major issues facing sport and its relationship with the EU. It is essential for those interested in sports law, the politics of sport and EU integration. It offers important insights into these debates and raises key questions concerning the appropriate theoretical tools for analysing European integration.